Active case-finding for tuberculosis by mobile teams in Myanmar: yield and treatment outcomes - Ohnmar Myint; Saw Saw; Petros Isaakidis; Mohammed Khogali; Anthony Reid; Nguyen Binh Hoa; Thi Thi Kyaw; Ko Ko Zaw; Tin Mi Mi Khaing; Si Thu Aung (BMC, 2017)
Abstract Background Since 2005, the Myanmar National Tuberculosis Programme (NTP) has been implementing active case finding (ACF) activities involving mobile teams in hard-to-reach areas. This study revealed the contribution of mobile team activities to total tuberculosis (TB) case detection, characteristics of TB patients detected by mobile teams and their treatment outcomes. Methods This was a descriptive study using routine programme data between October 2014 and December 2014. Mobile team activities were a one-stop service and included portable digital chest radiography (CXR) and microscopy of two sputum samples. The algorithm of the case detection included screening patients by symptoms, then by CXR followed by sputum microscopy for confirmation. Diagnosed patients were started on treatment and followed until a final outcome was ascertained. Results A total of 9 349 people with symptoms suggestive of TB were screened by CXR, with an uptake of 96.6%. Of those who were meant to undergo sputum smear microscopy, 51.4% had sputum examinations. Finally, 504 TB patients were identified by the mobile teams and the overall contribution to total TB case detection in the respective townships was 25.3%. Among total cases examined by microscopy, 6.4% were sputum smear positive TB. Treatment success rate was high as 91.8% in study townships compared to national rate 85% (2014 cohort). Conclusions This study confirmed the feasibility and acceptability of ACF by mobile teams in hard-to-reach contexts, especially when equipped with portable, digital CXR machines that provided immediate results. However, the follow-up process of sputum examination created a significant barrier to confirmation of the diagnosis. In order to optimize the ACF through mobile team activity, future ACF activities were needed to be strengthened one stop service including molecular diagnostics or provision of sputum cups to all presumptive TB cases prior to CXR and testing if CXR suggestive of TB.